Building Emergent Cycling Infrastructure During the COVID-19 Pandemic: The Case of Zapopan, México - Ohlund, Hannah; El-Samra, Siba; Amezola, Diana; Soto Morfín, Jesús Carlos; López Zaragoza, Carlos; Aguilar Gónzalez, Sonia (Frontiers in Sustainable Cities, 2022)
The COVID-19 pandemic has led to strict measures intended to limit people’s movement and slow viral spread. The subsequent need for social distancing when traveling has driven many cities to reduce public transport services, as urban residents simultaneously stay at home and avoid crowded spaces. As a result, cities are turning to cycling to meet the mobility needs of their inhabitants, particularly those who lack access to a private vehicle. Infrastructure plays a critical role in encouraging cycling by protecting cyclists and providing safe and comfortable conditions for users of various confidence levels. Due to the pandemic, this infrastructure has been rapidly constructed, in many cases, as pop-up or temporary installations. In this article, we present and examine the methods, design tools, and implementation processes used for building an emergent bike lane along Avenida Guadalupe in Zapopan, México during the COVID-19 pandemic. Through this examination, the paper distills and highlights the key features of a successful emergent bike lane in the urban Global South and identifies gaps in need of filling. The emergent intervention includes a number of traffic calming elements such as bollards and markings in addition to the two-directional 4.2 km extension of the bike lane, connecting the peripheral part of the city to the existing east cycle infrastructure. This case study shall contribute to a greater understanding of emergency mobility planning practices during crises such as the COVID-19 pandemic, as well as future directions for the expansion of cycling infrastructure and networks, especially in Latin America and the broader Global South.